THE DESCRIPTIVE STUDY OF CONSUMER NIGHT CULINARY BEHAVIOR IN SURABAYA - Anita Felicia (Perpustakaan Universitas Surabaya, 2018)
The aim of this research is to describe the consumer night culinary behavior in Surabaya. This descriptive research is using quantitative method by providing questionnaires and collecting the data. The sample consisted of 200 respondents whose age is 18 years old above and enjoy night culinary at least 4x a week in Surabaya. The result was analysed through descriptive statistics using SPSS 23.0. In the end, this research is providing a clear description about the consumer night culinary behavior in Surabaya, which give a positive impact for the night culinary providers. By understanding what consumer behavior is, they will have a broader view about new opportunities that arise from the changing of consumer behavior time by time.